1996
DOI: 10.1063/1.472121
|View full text |Cite
|
Sign up to set email alerts
|

Orientational behavior of solid nitrogen at high pressures investigated by vibrational Raman spectroscopy

Abstract: In this paper the results of an experimental study of the vibrational Raman shift of solid δ-, ε-, and β-nitrogen will be presented. The measurements have been performed in a diamond anvil cell, from 0.5 to 14 GPa and from 120 to 400 K. The accuracy of the spectroscopic measurements has been optimized in order to determine the Raman shift as a function of temperature on an isobar. As will be shown, measurements along an isobar are appropriate for obtaining information about the orientational behavior of the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 47 publications
3
16
0
Order By: Relevance
“…The coefficients of the fits through the data of the anisotropic, Etters, and core potential, next to the experimentally 19 determined coefficients, are given in Table I. Although the difference in coefficients is small, the results obtained with the Etters and anisotropic potential are in better agreement with experiment.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…The coefficients of the fits through the data of the anisotropic, Etters, and core potential, next to the experimentally 19 determined coefficients, are given in Table I. Although the difference in coefficients is small, the results obtained with the Etters and anisotropic potential are in better agreement with experiment.…”
Section: Discussionmentioning
confidence: 69%
“…The angle d depends on the angles of the unit cell. An extensive Raman study performed by Scheerboom and Schouten 18,19 revealed a second-order transition within the ␦ phase. Figure 3 shows the behavior of the frequencies of the spheres ( 1 ) and the disks ( 2 ) at 5.9 GPa.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11]. It can be seen directly that the decrease of the line width is for the greater part caused by the behavior of c :⌬ nitrogen and ⌬ argon decrease only Ϸ6% and Ϸ2%, respectively, while the correlation time is reduced to about half at the transition.…”
Section: Discussionmentioning
confidence: 87%
“…Unfortunately one cannot compare these results with the shift in solid pure nitrogen, i.e., the shift of one nitrogen molecule in a matrix of other nitrogen molecules, because of resonance coupling ͑RC͒. 8 At low pressure, this RC coupling is responsible for a continuous behavior of the shift at the fluid-solid ͑␤͒ phase transition. 11 At high pressure this RC is probably absent along the ␤-melting line.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation